Preparation method of primary magnet

By mixing magnetic raw materials with binder and introducing alloy additives with dispersions, the high cost and difficult process of coercive field strength improvement of rare earth permanent magnets in the prior art is solved, and the combination of high coercive field strength and economic cost is achieved.

CN120153439APending Publication Date: 2025-06-13MIMPLUS TECH GMBH & CO KG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380076590.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-04
Filing Date
2023-11-02
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, high production process difficulty, easy oxidation failure of fine-grained powders, and slow diffusion process speed in improving the coercive field strength of rare earth permanent magnets.

Method used

Green body is prepared by mixing the magnetic raw material with a binder, and the green body is treated with a dispersion containing a dispersion and a dispersion phase, alloy additive is introduced, and subsequently sintered to obtain the primary magnet.

Benefits of technology

The introduction of economical and evenly distributed alloy additives is achieved, which significantly improves the coercive field strength of the original magnet and can handle green bodies with wall thickness up to 40 mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120153439A_ABST
    Figure CN120153439A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a primary magnet (1), in which a magnetic starting material (3) is mixed with a binder (5), thereby obtaining a mixture (7) of the magnetic starting material (3) and the binder (5); producing a green body (9) from the mixture (7); treating the green body (9) with a dispersion (11) comprising at least one dispersant and a dispersed phase, at least one first substance (15) selected from the dispersant and the dispersed phase comprising an alloy additive for the primary magnet (1), thereby obtaining a treated green body (13); and sintering the treated green body (13) to obtain the primary magnet (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a primary magnet. Background Art

[0002] Rare earth permanent magnets made from primary magnets can be widely applied in various technical fields and are characterized by extremely high magnetic energy products. In particular, neodymium-iron-boron magnets have a magnetic energy product as high as 400 kJ / m 3 .

[0003] Especially in industrial applications, a key requirement for permanent magnets is that the permanent magnets have as high a coercive field strength as possible. The coercive field strength refers to the maximum magnetic field strength that needs to be overcome to avoid permanent damage to the permanent magnet when the permanent magnet is exposed to the action of a reverse magnetic field.

[0004] The coercive field strength of rare earth permanent magnets (especially neodymium-iron-boron magnets) shows temperature dependence, and the coercive field strength decreases with the increase in temperature. Therefore, in industrial applications, especially in situations that may face high-temperature environments, especially in motors, permanent magnets with high coercive field strength are preferably used.

[0005] The first way to increase the coercive field strength is to form an alloy by adding at least one rare earth element, especially at least one "heavy" rare earth element, such as dysprosium and / or terbium. However, its defect is that these elements are costly and will reduce the remanence of the permanent magnet at the same time.

[0006] The second way to increase the coercive field strength (compared with similar permanent magnets) is to prepare a structure with finer grains than similar permanent magnets. This structure can especially be achieved by using raw material powders with finer grains than similar permanent magnets. However, its defect is that such fine-grained powders, especially those with a particle size of less than 5 μm, are not only very difficult to prepare in terms of process technology, but also extremely prone to oxidation and failure, and the processing is challenging.

[0007] The third way to increase the coercive field strength is appropriate heat treatment, especially applicable to the preparation of permanent magnets by sintering. However, its defect is that the increase in the coercive field strength is very limited.

[0008] In addition, the grain boundary diffusion method (Grain Boundary Diffusion) can also be applied. A dispersion liquid containing active substances is directly coated on the sintered green body after sintering, after grinding / wire cutting, or after pickling for surface decontamination and reprocessing. These active substances contain at least one heavy rare earth element, and these elements diffuse into the interior of the permanent magnet along the grain boundaries during the subsequent heat treatment process. However, its defect is that the diffusion process is slow, resulting in economic feasibility only for permanent magnets with a wall thickness of at most 5 mm.

[0009] In addition, the powder blending method can also be used to prepare a green compact of neodymium iron boron permanent magnet by mixing different powders. The heavy rare earth element contents in the powders are different, and the particle sizes are also distributed differently. During the sintering process of the green compact, the heavy rare earth elements will be enriched in the grain boundary region. The defect of this powder blending method is that different powders are prone to agglomeration due to van der Waals force and / or magnetic attraction, so the mixing difficulty increases, resulting in uneven local distribution, making it difficult to fully utilize the heavy rare earth elements. Summary of the Invention

[0010] In view of the above, the object of the present invention is to provide a method for preparing a master magnet, especially a method for preparing a permanent magnet, which at least partially overcomes, preferably avoids the above defects, especially the defects in preparing permanent magnets.

[0011] By using the technical solutions of the present invention, especially the independent claims, dependent claims and the embodiments in the specification, the above technical problems can be solved.

[0012] To achieve the above object, the present invention provides a method for preparing a master magnet, in which a magnetic raw material is mixed with a binder to obtain a mixture of the magnetic raw material and the binder. Then, a green compact is prepared from the mixture. In addition, the green compact is treated with a dispersion containing at least one dispersant and a dispersed phase to obtain a treated green compact. Here, at least one first substance selected from the dispersant and the dispersed phase contains an alloy additive for the master magnet. Thereafter, the treated green compact is sintered to obtain the master magnet.

[0013] The advantages of the method are that the first substance (especially the alloy additive) can be introduced into the green compact in an economical and evenly distributed manner. By introducing the first substance, especially the alloy additive, at low cost, the cost of the master magnet can be reduced in the case where the alloy additive is expensive and scarce. In addition, compared with the magnets made by traditional processes, the advantages of the method also lie in that the magnetic properties (especially the coercive field strength) of the master magnet can be significantly improved (especially increased). In addition, the method can also be used to treat green compacts with a wall thickness of up to 40 mm. Advantageously, the first substance (especially the alloy additive) can diffuse between the particles of the magnetic raw material, especially along the grain boundaries between the particles into the interior of the green compact. More advantageously, the first substance (especially the alloy additive) can further diffuse into the interior of the particles of the magnetic raw material, so as to simultaneously increase the coercive field strength especially when using heavy rare earth elements as the alloy additive.

[0014] Particularly, the dispersion is composed of at least one dispersant and a dispersed phase.

[0015] Particularly, at least one first substance is an alloy additive. Particularly, at least one first substance consists of an alloy additive.

[0016] The first substance in the dispersion or alloy additive is particularly selected from the following group: rare earth elements (especially heavy rare earth elements, particularly dysprosium, terbium, holmium; light rare earth elements, particularly praseodymium, neodymium), rare earth element oxides, rare earth element hydrides, rare earth element nitrides, rare earth element carbides, rare earth element halides, copper-rare earth element compounds, aluminum-rare earth element compounds, zirconium-rare earth element compounds, gallium-rare earth element compounds, R x T y Tb alloys, dysprosium cobalt compounds, dysprosium terbium cobalt compounds, and terbium cobalt compounds.

[0017] Advantageously, the method is suitable for forming a powdered magnetic raw material based on a newly melted alloy (especially in the form of an ingot or melt-spun quenched material). Alternatively or additionally, the method is applicable to recycling magnetic materials and / or contaminated recycled magnetic materials. Additionally, it is preferred to alloy the recycled material with at least one rare earth element (preferably in powder form) to improve the properties of the recycled material.

[0018] The magnetic raw material can be in a pure state or a hydrogenated state. U.S. Patent Application US2013 / 0263699A1 and German Patent DE19843883C1 introduce the Hydrogen Decrepitation (HD) method to prepare a hydrogenated magnetic raw material through hydrogen-induced decay.

[0019] Preferably, the magnetic raw material is mechanically pulverized, especially by grinding, to obtain a powdered magnetic raw material with a particle size of 1 μm to 200 μm.

[0020] Preferably, the magnetic raw material remains partially or completely hydrogenated without dehydration treatment after grinding and / or before mixing with the binder. In particular, the magnetic raw material is in a hydrogenated state when mixed with the binder after grinding.

[0021] In an embodiment of the method, the volume fraction of the magnetic raw material in the mixture is at least 45% to at most 75%, and the volume fraction of the binder is at least 25% to at most 55%. The binder preferably contains at least one organic binder component.

[0022] In one embodiment, the binder comprises at least two, particularly at least three, binder components. In particular, the first binder component of the at least two binder components is a base polymer, which is particularly soluble in the pre-degreasing solvent and / or decomposable by the pre-degreasing acid. In addition, the second binder component of the at least two binder components is a backbone polymer, which is insoluble or hardly soluble in the pre-degreasing solvent and / or resistant to decomposition by the pre-degreasing acid. In particular, the solubility of the backbone polymer in the solvent is less than 1 g / L. Additionally, the backbone polymer preferably does not swell in the pre-degreasing solvent, so that the backbone polymer effectively maintains the stability of the green body until the green body is sintered. In particular, the binder comprises an additional base polymer, an additional backbone polymer, and / or a dispersant as the third binder component.

[0023] In particular, the binder comprises at least one substance selected from the group consisting of polyoxymethylene, polypropylene, paraffin wax, polyethylene, and polyamide. Advantageously, polyoxymethylene, polypropylene, paraffin wax, polyethylene, and polyamide are thermoplastic materials and are thus suitable for preparing green bodies. In addition, at least one substance selected from polyoxymethylene, polypropylene, paraffin wax, polyethylene, and polyamide can promote the orientation arrangement of magnetic raw material particles.

[0024] In particular, the binder consists of at least one substance selected from polyoxymethylene, polypropylene, paraffin wax, polyethylene, and polyamide and at least one backbone polymer.

[0025] In particular, at least one backbone polymer is polyethylene, especially LDPE. Alternatively or additionally, the base polymer is wax, especially paraffin wax. Alternatively or additionally, the dispersant is a surfactant, especially stearic acid.

[0026] In particular, the pre-degreasing treatment uses at least one non-polar organic solvent selected from the group consisting of n-heptane, n-hexane, and cyclohexane. Alternatively or additionally, the pre-degreasing treatment uses at least one polar organic solvent selected from the group consisting of acetone, isopropanol, and ethanol. Alternatively or additionally, the pre-degreasing treatment uses at least one acid selected from the group consisting of nitric acid, acetic acid, and oxalic acid.

[0027] In one technical solution, the binder includes polyethylene (especially LDPE) as the backbone polymer, wax (especially paraffin wax) as the base polymer, and a surfactant (especially stearic acid) as the dispersant. In addition, the pre-degreasing treatment uses a non-polar organic solvent, especially n-heptane.

[0028] In particular, the dispersion uses a colloidal dispersion system.

[0029] Particularly, a stable dispersion system is adopted. Under the technical background of the present invention, the stable dispersion system is characterized in that the sedimentation rate of the dispersed phase (especially the alloy additive for the raw magnet) in the earth's gravitational field is extremely slow, especially it will sediment after at least one hour, or will not sediment at all.

[0030] In one embodiment, the green body is treated with the dispersion at least twice, especially more than twice. Alternatively, the green body is first treated with the first dispersion at least once, and then treated with the second dispersion at least once, where the first dispersion and the second dispersion are different from each other. Particularly, the first dispersion includes the first alloy additive, and the second dispersion includes the second alloy additive, where the first alloy additive and the second alloy additive are different from each other. Alternatively or additionally, especially before sintering, the treated green body is treated with an additional substance (especially a liquid). Particularly, in multiple treatment steps, the green body is treated with multiple (especially different) dispersions and / or multiple (especially different) additional substances.

[0031] Particularly, a green body with a wall thickness of 0.4 mm to at most 10 mm is prepared and treated with the dispersion.

[0032] Particularly, the raw magnet is magnetized by a magnetic field (especially a magnetic pulse) to obtain a permanent magnet. Preferably, the magnetic flux density of the magnetic field (especially the magnetic pulse) is at least 2 Tesla, and particularly preferably at least 3 Tesla. Particularly, the method including this step is a method for preparing a permanent magnet.

[0033] According to the improvement of the present invention, the magnetic raw material uses a material containing R x T y B alloy particles. Preferably, the magnetic raw material uses a material composed of R x T y B alloy particles. Particularly preferably, the magnetic raw material uses a material containing Nd x Fe y B alloy particles or a material composed of Nd x Fe y B alloy particles.

[0034] Preferably, the magnetic raw material uses a material containing R x T y B alloy particles and rare earth-rich phase particles. Particularly preferably, the magnetic raw material is composed of a mixture of R x T y B alloy particles and rare earth-rich phase particles. Preferably, the magnetic raw material uses a material containing Nd x Fe y B alloy particles and neodymium-rich phase particles or a material composed of such particles. Particularly preferably, the magnetic raw material contains Nd x Fe yThe mixture consists of or is composed of B alloy particles and neodymium-rich phase particles.

[0035] In the context of the present invention, R represents a rare earth element, T represents at least one element selected from iron and cobalt, and B represents boron. In particular, the iron element and the cobalt element can be partially or completely substituted for each other, so that only iron or cobalt or any mixture of iron and cobalt exists. Preferably, the rare earth element is neodymium. In a preferred embodiment, R x T y The B alloy additionally contains additional elements, preferably metals, especially transition metals, selected from the group consisting of: aluminum, copper, zirconium, gallium, hafnium, and niobium, preferably in trace amounts.

[0036] Preferably, the magnetic raw material includes Nd 2 Fe 14 B alloy particles or is composed of Nd 2 Fe 14 B alloy particles.

[0037] Preferably, the rare earth-rich phase (especially the neodymium-rich phase) contains at least one rare earth element (especially neodymium) or a compound of the rare earth element (especially neodymium). Additionally preferably, the rare earth-rich phase (especially the neodymium-rich phase) contains at least one other R x T y B alloy (especially Nd x Fe y B alloy) element. Alternatively or additionally, at least one rare earth element (especially neodymium) is in a hydrogenated state. Preferably, the neodymium-rich phase includes NdH 2 and / or NdH 2,7 or is composed of NdH 2 and / or NdH 2,7 . Alternatively, in a preferred technical solution, the rare earth-rich phase (especially the neodymium-rich phase) can be composed of at least one rare earth element (especially neodymium) or a compound of the rare earth element (especially neodymium).

[0038] The rare earth-rich phase is preferably formed in the original magnet structure, especially in the permanent magnet structure obtained from the original magnet, and is distributed at the grain boundaries of the structure.

[0039] According to an improved solution of the present invention, an external magnetic field is applied to the green body during the preparation of the green body. Alternatively or additionally, an external magnetic field is applied to the green body after the preparation of the green body. Advantageously, during and / or after the preparation of the green body, the dipoles of the magnetic raw material are aligned in parallel by externally applying a magnetic field.

[0040] Preferably, a magnetic field is applied to the green body before treating the green body with the dispersion.

[0041] Preferably, the externally applied magnetic field is generated by a switchable electromagnet and / or a permanent magnet.

[0042] In a certain technical solution, a green compact is prepared in an externally applied magnetic field. Advantageously, during the preparation of the green compact, the magnetic raw material particles for preparing the green compact are self-aligned according to the externally applied magnetic field. Preferably, the magnetic raw material used for the green compact is hard magnetic. In particular, an external magnetic field is applied to the green compact only during the preparation of the green compact. In particular, no external magnetic field is applied to the green compact after the preparation of the green compact.

[0043] In another technical solution, an external magnetic field is applied to the green compact after the preparation of the green compact. In particular, an external magnetic field is applied to the green compact only after the preparation of the green compact. In particular, no external magnetic field is applied to the green compact during the preparation of the green compact.

[0044] In another technical solution, an external magnetic field is applied to the green compact during and after the preparation of the green compact.

[0045] Preferably, during the application of the external magnetic field, the green compact is heated to the softening temperature of the mixture.

[0046] According to an improved solution of the present invention, the green compact is pre-degreased before being treated with the dispersion. Alternatively or additionally, the green compact is pre-degreased during the treatment with the dispersion. Alternatively or additionally, the treated green compact is degreased before sintering. In particular, during pre-degreasing, the soluble binder component is leached out of the green compact, advantageously enabling the green compact to form at least a partially open-pored surface, especially a fully open-pored surface. In particular, the porosity of the obtained green compact is at least 30 vol.%, preferably at least 40 vol.%, preferably at least 50 vol.%, particularly preferably at least 55 vol.% to at most 60 vol.%. Advantageously, after pre-degreasing, the skeletal polymer in the binder remains in the green compact. The skeletal polymer will advantageously enhance the mechanical stability of the green compact.

[0047] The at least partially open-pored surface and / or open-pored structure of the green compact advantageously allows the dispersion (especially the first substance, especially the alloy additive) to penetrate rapidly and uniformly into the green compact. More advantageously, the dispersion (especially the first substance, especially the alloy additive) can freely diffuse into the green compact during an optional subsequent heat treatment process.

[0048] In particular, solvent degreasing is used for pre-degreasing.

[0049] If the dispersion treatment is carried out after pre-degreasing, the green compact has an open-pored structure and the dispersion easily enters the pore channels of the green compact.

[0050] If pre-degreasing and dispersion treatment are carried out simultaneously, the soluble organic binder components are leached out of the green compact, and at the same time the first substance (especially the alloy additive) diffuses into the pore channels of the green compact.

[0051] In a preferred embodiment of the method, the binder is at least partially removed from the green body by a solvent (especially an organic solvent), in particular by solvent extraction or other chemical methods. Alternatively or additionally, the residual binder is removed from the treated green body by thermal decomposition, especially directly before sintering. Alternatively, during sintering, the residual binder is removed from the treated green body by thermal decomposition.

[0052] In an alternative embodiment, before pre-degreasing and / or degreasing the green body, the green body is treated with a dispersion, especially by dispersion coating.

[0053] According to an improvement of the present invention, the green body is pre-degreased at a predetermined duration, a predetermined pressure and a predetermined temperature.

[0054] In particular, the predetermined temperature is at least equal to room temperature, especially 25 °C, and the predetermined temperature is especially at least 30 °C. Alternatively or additionally, the predetermined temperature is at most as high as such that the predetermined temperature is at least 10 °C lower than the boiling point of the solvent used for pre-degreasing at the predetermined pressure.

[0055] In particular, the predetermined pressure is at least 50 mbar lower than the ambient pressure to at most 50 mbar higher than the ambient pressure. Preferably, the predetermined pressure is approximately equal to the ambient pressure, especially equal to the ambient pressure.

[0056] In particular, the predetermined duration is from at least 1 hour to at most 72 hours.

[0057] According to an improvement of the present invention, before sintering, the treated green body is dried.

[0058] In one embodiment, after the first treatment of the green body with a dispersion and / or after the treatment of the green body with a first dispersion, the green body is dried. In particular, before the second treatment of the green body with a dispersion and / or a second dispersion, the green body is dried.

[0059] In another embodiment, before treating the treated green body with an additional substance, the treated green body is dried.

[0060] According to an improvement of the present invention, the dispersion is a suspension or an aerosol. In particular, the second substance selected from the dispersant and the dispersed phase in the dispersion is selected from the group consisting of: a solvent, air, nitrogen, argon and helium. The first substance in the dispersion is selected from the group consisting of: rare earth elements (especially heavy rare earth elements, especially dysprosium, terbium, holmium; light rare earth elements, especially praseodymium, neodymium), rare earth element oxides, rare earth element hydrides, rare earth element nitrides, rare earth element carbides, rare earth element halides, copper-rare earth element compounds, aluminum-rare earth element compounds, zirconium-rare earth element compounds, gallium-rare earth element compounds, R containing heavy rare earth elements x T yB alloys, dysprosium cobalt compounds, dysprosium terbium cobalt compounds, and terbium cobalt compounds.

[0061] If a heavy rare earth element is used as an alloy additive, especially as the first substance, the coercive field strength will increase significantly because the heavy rare earth element is enriched at the grain boundaries during the sintering process. Alternatively or additionally, when the heavy rare earth element diffuses into the magnetic raw material particles, the coercive field strength will also increase.

[0062] If a copper compound (especially a copper-rare earth element compound, particularly a copper-rare earth element alloy) or an aluminum compound (especially an aluminum-rare earth element compound, particularly an aluminum-rare earth element alloy) is used as an alloy additive (especially as the first substance), then especially the layer thickness of the rare earth-rich phase increases during the sintering process, thereby also increasing the coercive field strength.

[0063] If a zirconium compound (especially a zirconium-rare earth element compound, particularly a zirconium-rare earth element alloy) is used as an alloy additive (especially as the first substance), then especially during the sintering process, the grain growth can be advantageously reduced and / or inhibited.

[0064] If a gallium compound (especially a gallium-rare earth element compound, particularly a gallium-rare earth element alloy) is used as an alloy additive (especially as the first substance), then especially after sintering, the rare earth-rich phase has an amorphous structure, thereby advantageously enhancing the coercive field strength.

[0065] According to the improvement scheme of the present invention, the solvent is a compound selected from the group consisting of: cyclohexane, n-hexane, n-heptane, paraffin oil, acetone, isopropanol, ethanol, and organic solvents.

[0066] In particular, the solvent is a non-polar solvent, especially an organic solvent.

[0067] According to the improvement scheme of the present invention, the first substance in the dispersion is in the form of particles with a particle size of at least 0.001 μm to at most 30 μm. Alternatively or additionally, the volume fraction of the first substance in the dispersion is at least 1% to at most 70%.

[0068] In particular, at the beginning of the method, the first substance is in the form of particles with a particle size of at least 0.001 μm to at most 30 μm. Alternatively, the first substance is processed by a grinding process (especially as a sub-step of the method) to generate particles with a particle size of at least 0.001 μm to at most 30 μm. Preferably, the grinding process is carried out by a device selected from the group consisting of: jet mills, ball mills, and attrition mills.

[0069] According to the improvement scheme of the present invention, the process of treating the green body with the dispersion is selected from the following group: spraying (especially by means of a spray gun), brushing (especially by means of a brush and / or a coating roller), dipping, printing (especially pad printing and / or screen printing), and slot coating. Advantageously, the green body (especially after pre-degreasing and especially after opening pores) is infiltrated with the dispersion.

[0070] In one embodiment, the green body is immersed in the dispersion so that the green body is completely wrapped by the dispersion. In particular, the dispersion contains alloy additives and a solvent. In particular, the dispersion consists of alloy additives and a solvent. In particular, the green body is immersed in the dispersion for at least 1 second to at most 24 hours, especially so that the green body is wrapped by the dispersion.

[0071] In another embodiment, the green body is coated with the dispersion, especially the entire surface of the green body is coated with the dispersion. In particular, the green body is sprayed and / or coated with the dispersion. In particular, the dispersion contains alloy additives and at least one gas selected from the following group: air and inert gases, especially nitrogen, argon, and helium. In particular, the dispersion consists of alloy additives and at least one gas selected from the following group: air and inert gases, especially nitrogen, argon, and helium. In particular, the green body is sprayed with the dispersion for a duration of at least 1 second to at most 30 seconds.

[0072] According to the improvement scheme of the present invention, the process for preparing the green body is selected from the following group: injection molding (especially metal powder injection molding), additive manufacturing, extrusion, and wet pressing.

[0073] In one embodiment of the method, the green body is prepared by injection molding a mixture containing a magnetic raw material and especially an organic binder. Alternatively, the green body is prepared by injection molding a mixture consisting of a magnetic raw material and an organic binder.

[0074] In another embodiment of the method, the green body is prepared by wet pressing a magnetic raw material. In wet pressing, the binder uses an organic solvent, preferably a volatile non-polar and / or polar organic solvent. The volatile non-polar and / or polar organic solvents are selected from the following group: alcohols, acyclic hydrocarbons, cycloalkanes, ketones, and other mixtures of volatile organic substances that can act as solvents. Preferably, the alcohol is ethanol or isopropanol. Preferably, the cycloalkane is cyclohexane. Preferably, the ketone is acetone. The mixture of volatile organic substances is preferably selected from the following group: petroleum, white oil, and light gasoline. In addition, it is preferred to dry the green body before sintering.

[0075] According to the improvement scheme of the present invention, the treated green body is sintered in a vacuum. Alternatively, the treated green body is sintered in an atmosphere containing at least one process gas selected from the group consisting of argon and helium. Alternatively, the treated green body is sintered in an atmosphere consisting of at least one process gas selected from the group consisting of argon and helium. Advantageously, during the sintering process, the magnetic raw material particles (especially R x T y B particles) are alloyed with the alloy additive, thereby significantly improving the magnetic properties of the original magnet, especially the coercive field strength.

[0076] In the technical background of the present invention, "vacuum" refers to an atmosphere environment with an absolute pressure lower than 1·10 -3 mbar.

[0077] In particular, the green body is sintered in a helium atmosphere. Alternatively, the green body is sintered in an argon atmosphere. Alternatively, the green body is sintered in an argon-helium atmosphere. In particular, the atmosphere is selected from a helium atmosphere, an argon atmosphere, and an argon-helium atmosphere, and the atmosphere pressure is at least 1·10 -3 mbar higher than the ambient pressure to at most 200 mbar. In the technical background of the present invention, the helium atmosphere especially refers to a gas composed of pure helium and at most 5 vol.% impurities.

[0078] In the technical background of the present invention, the argon atmosphere especially refers to a gas composed of pure argon and at most 5 vol.% impurities.

[0079] In the technical background of the present invention, the argon-helium atmosphere especially refers to a gas composed of pure argon, pure helium, and at most 5 vol.% impurities.

[0080] In particular, the green body is sintered at a sintering temperature of at least 950 °C to at most 1200 °C, preferably at least 1000 °C to at most 1100 °C.

[0081] In one embodiment of the method, during the sintering process, the treated green body is heated from room temperature or the degreasing temperature to the sintering temperature at a heating rate of at least 0.1 K / min to at most 10 K / min. During the heating of the treated green body, preferably at least one holding stage at a predetermined intermediate temperature is provided, especially multiple holding stages at a plurality of predetermined intermediate temperatures. The temperature in the at least one holding stage is kept constant for a predetermined duration, and the holding duration is preferably at least 30 minutes to at most 1200 minutes. In particular, the at least one intermediate temperature is at least 450 °C to at most 900 °C, preferably at least 700 °C to at most 800 °C. Advantageously, in the at least one holding stage, the magnetic raw material particles (especially R x T y B particles) are pre-alloyed with the alloy additive. In one embodiment of the method, the holding stage promotes the diffusion of the alloy additive along the grain boundaries or surfaces of the magnetic raw material into the interior of the green body.

[0082] The present invention also includes a raw magnet prepared by the method of the present invention or by the method according to one or more of the foregoing embodiments, in particular a permanent magnet obtained after magnetizing the raw magnet.

[0083] The present invention also includes the use of such a permanent magnet in a device selected from the group consisting of: electric motors, loudspeakers, microphones, generators, hard disk drives, and sensors.

[0084] The present invention also includes a device selected from the group consisting of an electric motor, a loudspeaker, a microphone, a generator, a hard disk drive, and a sensor, the device comprising a permanent magnet prepared by the method of the present invention or by the method according to one or more of the foregoing embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] The present invention will be described in detail below with reference to the accompanying drawings. In the drawings:

[0086] Figure 1 A flowchart showing an embodiment of a method for preparing a raw magnet is shown;

[0087] Figure 2 A schematic diagram showing an embodiment of the preparation of a raw magnet is shown. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0088] Figure 1 A flowchart showing an embodiment of a method for preparing a raw magnet 1 is shown.

[0089] In the first step a), the magnetic raw material 3 is mixed with the binder 5 to obtain a mixture 7 of the magnetic raw material 3 and the binder 5.

[0090] In particular, the magnetic raw material 3 is a material comprising R x T y B alloy particles. Alternatively, the magnetic raw material 3 is a material consisting of R x T y B alloy particles. Alternatively, the magnetic raw material 3 is a material comprising Nd x Fe y B alloy particles or a material consisting of Nd x Fe y B alloy particles.

[0091] Preferably, the volume fraction of the magnetic raw material 3 in the mixture 7 is at least 40% to at most 75%, and the volume fraction of the binder 5 is at least 25% to at most 55%. The binder 5 preferably comprises at least one organic binder component.

[0092] In the second step b), a green compact 9 is prepared from the mixture 7. In particular, the preparation process of the green compact 9 is selected from the group consisting of: injection molding (especially metal powder injection molding), additive manufacturing, extrusion, and wet pressing.

[0093] In particular, in the second step b), especially during the preparation of the green body 9, an external magnetic field is applied to the green body 9.

[0094] In the third step c), the green body 9 is treated with a dispersion 11 containing at least one dispersant and a dispersed phase to obtain a treated green body 13. Alternatively, in the third step c), the green body 9 is treated with a dispersion 11 composed of at least one dispersant and a dispersed phase to obtain a treated green body 13.

[0095] Herein, at least one first substance 15 selected from the dispersant and the dispersed phase contains alloy additives for the primary magnet 1. In particular, at least one first substance 15 selected from the dispersant and the dispersed phase consists of alloy additives.

[0096] In particular, in the third step c), the process of treating the green body 9 with the dispersion 11 is selected from the following group: spraying (especially by means of a spray gun), brushing (especially by means of a brush and / or a coating roller), dipping, printing (especially pad printing and / or screen printing), and slot coating.

[0097] In particular, a colloidal dispersion system and / or a stable dispersion system is used as the dispersion 11.

[0098] In particular, a suspension or an aerosol is used as the dispersion 11.

[0099] In particular, the first substance 15 in the dispersion 11 is selected from the following group: rare earth elements (especially heavy rare earth elements, in particular dysprosium, terbium, holmium; light rare earth elements, in particular praseodymium, neodymium), rare earth element oxides, rare earth element hydrides, rare earth element nitrides, rare earth element carbides, rare earth element halides, copper-rare earth element compounds, aluminum-rare earth element compounds, zirconium-rare earth element compounds, gallium-rare earth element compounds, R x T y B alloys, dysprosium cobalt compounds, dysprosium terbium cobalt compounds, and terbium cobalt compounds. Alternatively or additionally, the first substance 15 in the dispersion 11 is in particulate form, with a particle size of at least 0.001 μm to at most 30 μm. Alternatively or additionally, the volume fraction of the first substance 15 in the dispersion 11 is at least 1% to at most 70%.

[0100] In particular, the second substance 17 selected from the dispersant and the dispersed phase in the dispersion 11 is selected from the following group: solvents, air, nitrogen, argon, and helium. In particular, the solvent uses compounds selected from the following group: cyclohexane, n-hexane, n-heptane, paraffin oil, acetone, isopropanol, ethanol, and organic solvents.

[0101] In particular, in the third step c), especially during the treatment with the dispersion 11, the green compact 9 is pre-degreased. In particular, the green compact 9 is pre-degreased at a predetermined duration, a predetermined pressure, and a predetermined temperature.

[0102] Optionally, the third step c) is carried out at least twice, especially more times. Thereby, the green compact 9 is treated with the dispersion 11 and / or with mutually different dispersions 11 (especially the first dispersion and the second dispersion) at least twice, especially more times. In particular, the first dispersion contains a first kind of first substance, and the second dispersion contains a second kind of first substance, where the first kind of first substance is different from the second kind of first substance.

[0103] In the fourth step d), the treated green compact 13 is sintered to obtain the raw magnet 1. In particular, the treated green compact 13 is sintered in a vacuum. Alternatively, the treated green compact 13 is sintered in an atmosphere containing at least one process gas selected from the group consisting of argon and helium.

[0104] In an optional manufacturing step carried out after the fourth step d), the raw magnet is magnetized by a magnetic field (especially a magnetic pulse) to obtain a permanent magnet. Preferably, the magnetic flux density of the magnetic field (especially the magnetic pulse) is at least 2 teslas, and particularly preferably at least 3 teslas.

[0105] In an optional fifth step e), after the second step b), especially after preparing the green compact 9, and before the third step c), especially before treating the green compact 9 with the dispersion 11, an external magnetic field is applied to the green compact 9.

[0106] In an optional first sixth step f1), after the second step b), especially after preparing the green compact 9, and before the third step c), especially before treating the green compact 9 with the dispersion 11, the green compact 9 is pre-degreased.

[0107] Preferably, the first sixth step f1) is carried out after the fifth step e). However, the first sixth step f1) can also be carried out before or simultaneously with the fifth step e).

[0108] In an optional second sixth step f2), before the fourth step d), especially before sintering, the treated green compact 13 is degreased, especially by thermal degreasing.

[0109] In an optional first seventh step g1), before the fourth step d), especially before sintering, the treated green compact 13 is dried.

[0110] Optional second seventh step g2), drying the processed green body 13 before restarting the third step c), in particular before reprocessing with the dispersion 11 and / or before processing with an additional dispersion 11.

[0111] Figure 2 The schematic diagram of the embodiment for preparing the original magnet 1 is shown.

[0112] In each figure, the same elements with equivalent functions are marked with the same reference numerals, so their descriptions can be referred to the foregoing content.

[0113] Figure 2 a) shows the mixture 7 of the magnetic raw material 3 (preferably an R x T y B alloy, in particular an Nd x Fe y B alloy) and the organic binder 5 in particular. Preferably, the process for preparing the green body 9 from the mixture 7 is selected from the group consisting of: injection molding, additive manufacturing, extrusion, and wet pressing.

[0114] Figure 2 b) shows the green body 9 after pre-degreasing (in particular after at least partially removing the organic binder 5). In particular, during pre-degreasing, the soluble binder components of the binder 5 are dissolved out of the green body 9, so that the green body 9 forms a surface with at least partially open pores, in particular a completely open surface. In particular, after pre-degreasing, the backbone polymer 19 in the binder 5 remains in the green body 9.

[0115] For clarity, only one particle of the magnetic raw material 3 is marked with a reference numeral in the figure.

[0116] Figure 2 c) shows the green body 9 during processing with the dispersion 11. In particular, Figure 2 the green body 9 in c) is infiltrated by the dispersion 11, that is, the dispersion 11 penetrates into the pores of the green body 9.

[0117] For clarity, only one particle of the magnetic raw material 3 and one backbone polymer 19 are marked with reference numerals in the figure.

[0118] Figure 2 d) shows the processed green body 13, in particular the processed green body 13 after drying. The first substance 15 is embedded in particulate form between the particles of the magnetic raw material 3 and the backbone polymer 19.

[0119] Figure 2 e) shows the original magnet 1 after sintering. The particles of the magnetic raw material 3 aggregate into grains 21, in particular R x T y B grains. In particular, each particle 21 is coated with the first substance 15.

Claims

1. A method for preparing a raw magnet (1), wherein, - mixing a magnetic raw material (3) with a binder (5) to obtain a mixture (7) of the magnetic raw material (3) and the binder (5); - preparing a green body (9) from the mixture (7); - treating the green body (9) with a dispersion (11) that contains at least one dispersant and a dispersed phase, wherein at least one first substance (15) selected from the dispersant and the dispersed phase contains an alloy additive for the raw magnet (1) to obtain a treated green body (13); - sintering the treated green body (13) to obtain the raw magnet (1).

2. The method according to claim 1, wherein, The magnetic raw material (3) is a material comprising R x T y B alloy particles and preferably comprising rare-earth-rich phase particles.

3. The method according to any one of the above claims, wherein, An external magnetic field is applied to the green body (9) during and / or after the preparation of the green body (9).

4. The method according to any one of the above claims, wherein, - the green body (9) is pre-degreased before and / or during the treatment with the dispersion (11); and / or - the treated green body (13) is degreased before sintering.

5. The method according to any one of the above claims, wherein, The green body (9) is pre-degreased at a predetermined duration, predetermined pressure, and predetermined temperature.

6. The method according to any one of the above claims, wherein, The treated green body (13) is dried before sintering.

7. The method according to any one of the above claims, wherein, - the dispersion (11) is a suspension or an aerosol; - a second substance (17) selected from the dispersant and the dispersed phase in the dispersion (11) is selected from the group consisting of: a solvent, air, nitrogen, argon, and helium; - The first substance (15) is selected from the group consisting of: rare earth elements, especially heavy rare earth elements, in particular dysprosium, terbium, holmium, light rare earth elements, especially praseodymium, neodymium; rare earth element oxides; rare earth element hydrides; rare earth element nitrides; rare earth element carbides; rare earth element halides; copper-rare earth element compounds; aluminum-rare earth element compounds; zirconium-rare earth element compounds; gallium-rare earth element compounds; R x T y B alloys; dysprosium cobalt compounds; dysprosium terbium cobalt compounds and terbium cobalt compounds.

8. The method according to any one of the above claims, wherein, The solvent is a compound selected from the group consisting of: cyclohexane, n-hexane, n-heptane, paraffin oil, acetone, isopropanol, ethanol, and an organic solvent.

9. The method according to any one of the above claims, wherein, - the first substance (15) in the dispersion (11) is in the form of particles with a particle size of at least 0.001 μm to at most 30 μm; and / or - the volume fraction of the first substance (15) in the dispersion (11) is at least 1% to at most 70%.

10. The method according to any one of the above claims, wherein, The process of treating the green body (9) with the dispersion (11) is selected from the group consisting of: spraying, especially by means of a spray gun; brushing, especially by means of a brush and / or a coating roller; dipping; printing, especially pad printing and / or screen printing; and slot coating.

11. The method according to any one of the above claims, wherein, The process for preparing the green body (9) is selected from the group consisting of: injection molding, additive manufacturing, extrusion, and wet pressing.

12. The method according to any one of the above claims, wherein, The treated green body (13) is sintered in a vacuum or in an atmosphere containing at least one process gas, and the process gas is selected from the group consisting of: argon and helium.

Citation Information

Patent Citations

  • Method for recycling of permanent magnets forming part of scrap material

    DE19843883C1

  • Magnet Recycling

    US20130263699A1